论析《延禧攻略》中的女性团结现象 = A study of Chinese period drama series, The Story of Yanxi Palace from the perspective of women's solidarity in feminism - 钟凯乐 Chong, Claire Kaile (Nanyang Technological University, 2022)
尽管谷歌（Google）被中国政府所屏蔽，但宫斗剧《延禧攻略》却在2018年全球谷歌搜寻的电视剧中，高居第一名。该剧之所以能在众多宫斗剧中脱颖而出，其原因包括鲜明的人物刻画、制作团队对清朝史实作出足够的历史考察和还原。但更值得一提的是，它更多注重在女性之间的姐妹情谊。为此，本文意在探讨《延禧攻略》所体现的，女性主义论述下的“女性团结”。 本文第一章会先以2018年中国的 #MeToo女权运动解释《延禧攻略》和女性主义的关联，并以此为基础，介绍女性团结的范畴和定义女性团结。第二章将沿着女性主义的框架，对《延禧攻略》中的女性团结作出归类和探讨。第三章会通过性别压迫的角度，分析这些团结对反抗父权的作用。关键词：《延禧攻略》；女性主义；女性团结 Among the many dramas aired in 2018, Chinese period drama series The Story of Yanxi Palace emerged victorious as the most googled drama in that year, despite it being from a country where its government has blocked Google’s search engine. How it had managed to stand out from its competitors could be attributed to not only the unconventional portrayal of the characters, and the production team’s efforts at restoring the Qing history and artifacts, but also its focus on the sisterhood among the female characters throughout the show. As such, the objective of this thesis will revolve around the study of women’s solidarity in feminism in The Story of Yanxi Palace. The first chapter of this thesis will explore the connection between The Story of Yanxi Palace and feminism, through the 2018 #MeToo movement in China, before introducing and defining women’s solidarity. The second chapter will base on the theory of feminism and categorise the relationships between the female characters into different types of solidarities. Lastly, the third chapter will analyse the effect of resistance against the patriarchal system by the different groups of female solidarities throughout the series. Keywords: The Story of Yanxi Palace, Feminism, Women’s Solidarity